2013
DOI: 10.1152/jn.00656.2012
|View full text |Cite
|
Sign up to set email alerts
|

Allocation of attention across saccades

Abstract: Whenever the eyes move, spatial attention must keep track of the locations of targets as they shift on the retina. This study investigated transsaccadic updating of visual attention to cued targets. While observers prepared a saccade, we flashed an irrelevant, but salient, color cue in their visual periphery and measured the allocation of spatial attention before and after the saccade using a tilt discrimination task. We found that just before the saccade, attention was allocated to the cue's future retinal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(143 citation statements)
references
References 75 publications
17
123
0
Order By: Relevance
“…However, it is unlikely that the predictability of the saccade contributed to faster remapping, as other studies have found that attention is predictively remapped in advance of a saccade using unpredictable saccades (Jonikaitis et al, 2013;Rolfs et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it is unlikely that the predictability of the saccade contributed to faster remapping, as other studies have found that attention is predictively remapped in advance of a saccade using unpredictable saccades (Jonikaitis et al, 2013;Rolfs et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…One mechanism that has been proposed to explain this ability consists in the updating (remapping) of target locations to compensate for each eye movement. This process has been documented physiologically in saccade and attention areas (Duhamel, Colby, & Goldberg, 1992;Fecteau & Munoz, 2006;Sommer & Wurtz, 2006;Wurtz, Joiner, & Berman, 2011) and has been demonstrated behaviorally with probes that reveal the location of attentional benefits before and after eye movements (Hunt & Cavanagh, 2011;Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Rolfs, Jonikaitis, Deubel, & Cavanagh, 2011). A number of review papers have suggested that the remapping process offers a sparse form of visual constancy by predicting where targets will be in retinotopic coordinates following each eye movement (Berman & Colby, 2009;Cavanagh, Hunt, Afraz, & Rolfs, 2010;Hall & Colby, 2011;Mathôt & Theeuwes, 2011;Wurtz, 2008).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Predictive Table 1 Mean RTs and error rates at the cued location, the remapped location, the future retinal location, and corresponding control locations neuronal discharges that have been observed in multiple brain regions generally occur within about 100 ms before saccade onset (e.g., Duhamel et al, 1992;Umeno & Goldberg, 1997;Walker et al, 1995). In the non-IOR behavioral studies mentioned in the introduction, robust effects also are consistently observed at the remapped location only within 100 ms before saccade onset (e.g., Harrison et al, 2013;Hunt & Cavanagh, 2011;Jonikaitis et al, 2013;Rolfs et al, 2011). Although remapped neuronal responses have been shown in all regions that have been linked to IOR, available evidence seems to suggest that environmental IOR is most likely mapped in parietal regions.…”
Section: Discussionmentioning
confidence: 97%
“…Error bars represent ± 1 SEM. **p < 0.01 that it could be a mechanism underlying spatial attention (Jonikaitis, Szinte, Rolfs, & Cavanagh, 2013;Rolfs, Jonikaitis, Deubel, & Cavanagh, 2011).…”
Section: Introductionmentioning
confidence: 95%